ISSUES OF IMPROVING THE NORMS RELATED TO ADDITIONAL PUNISHMENTS IN THE NATIONAL LEGISLATION (World Bulletin of Management and Law, 2023)
This article analyzes the issues of improving the norms related to additional punishments in the national legislation. In this regard, attention is focused on the views of national and foreign scientists on the nature of the additional punishment defined in the current criminal law, the norms established in this regard in the national legislation, and the explanations recorded in the decisions of the Plenum of the Supreme Court of the Republic of Uzbekistan on this issue. The reforms carried out in our Republic in recent years on the improvement of the institution of additional punishments have been analyzed. Based on the research, the system of additional punishments in the Criminal Code was revised. In particular, changing the name of the punishment "deprivation of a military or special title" provided for in the Criminal Code to "deprivation of a state award, military or special title, qualification or rank of the Republic of Uzbekistan", it is proposed to introduce a new type of additional penalty called "expulsion of a foreign citizen or stateless person from the territory of the Republic of Uzbekistan"